Redefining Khilafah: Integrating Islamic Responsibility and Democratic Ethics - Shofiyullah, Saifiddaulah; Syaefullah, Syaefullah; Giling, Mustamin; Baldan Haramain, Fathur (LPPM IAIN Kudus, 2025)
This study examines the long-debated relationship between khilafah (caliphate) and democracy, which are often viewed as two opposing political poles. The issue arises because both concepts are frequently interpreted solely as systems or forms of government, leading to a reductive understanding. While democracy has an established framework as a political system, the notion of the caliphate has been shaped by ideological biases. As a result, both supporters and critics of the caliphate have misconstrued its Qur’anic meaning, perpetuating the misconception that the caliphate represents a specific political structure. This research seeks to clarify the original meaning of khilafah beyond political interests and to explore the possibility of reconciling it with democratic principles. Using the thematic interpretation method to uncover the Qur’anic conception of the caliphate and Kuntowijoyo’s Prophetic Social Science as an analytical framework, this study finds that khilafah is not a state system but a divine moral character that reflects human responsibility to emulate God’s attributes. Furthermore, the caliphate should be understood as an intellectual and ethical movement grounded in knowledge, rather than as a doctrinal or institutional form of governance.